2011
DOI: 10.1073/pnas.1105315108
|View full text |Cite
|
Sign up to set email alerts
|

Coordinate linkage of HIV evolution reveals regions of immunological vulnerability

Abstract: Cellular immune control of HIV is mediated, in part, by induction of single amino acid mutations that reduce viral fitness, but compensatory mutations limit this effect. Here, we sought to determine if higher order constraints on viral evolution exist, because some coordinately linked combinations of mutations may hurt viability. Immune targeting of multiple sites in such a multidimensionally conserved region might render the virus particularly vulnerable, because viable escape pathways would be greatly restri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
263
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 189 publications
(274 citation statements)
references
References 33 publications
7
263
2
Order By: Relevance
“…The lack of correlation between HR-AIDS and the density of the amino acid covariation network associated with any given site under immune selection suggests that targeting structural or functional "network hubs" (i.e., those exhibiting higher-order evolutionary constraints within a given HIV protein [33]) is not independently protective. Similarly, the lack of correlation between HR-AIDS and average sequence conservation of sites under HLA selection indicates that the ability to target constrained sites is not in itself protective: it may depend on where these sites are in the HIV-1 proteome and how strongly they are targeted.…”
Section: Discussionmentioning
confidence: 99%
“…The lack of correlation between HR-AIDS and the density of the amino acid covariation network associated with any given site under immune selection suggests that targeting structural or functional "network hubs" (i.e., those exhibiting higher-order evolutionary constraints within a given HIV protein [33]) is not independently protective. Similarly, the lack of correlation between HR-AIDS and average sequence conservation of sites under HLA selection indicates that the ability to target constrained sites is not in itself protective: it may depend on where these sites are in the HIV-1 proteome and how strongly they are targeted.…”
Section: Discussionmentioning
confidence: 99%
“…More generally, apart from the phenomenon of elite control, strong T cell responses against the gene product Gag have been associated with control of viremia, while those targeting Env are associated with rapid progression (77). Although these observations are related to targeting of viral regions that cannot tolerate mutations (78,79), high-avidity IFN-γ-expressing CD8 + T cells targeted against nonescaped epitopes also persist in cases of poor virologic control. These and other lines of evidence have led to an appreciation for the considerable heterogeneity in the antiviral functionalities of HIV-specific CD8 + T cell responses, giving rise to the paradigm of "driver" CD8 + T cell responses, which lead to control over viral replication and/or selection of escape mutations, versus "passenger" required to clear viral reservoirs at tissue sites of viral reactivation and how this relates to frequencies of HIV-specific CD8 + T cells in the peripheral blood.…”
Section: + T Cell-mediated Eradicationmentioning
confidence: 99%
“…In the setting of active viremia, it is critical that CD8 + T cells target a conserved epitope, such that either escape cannot occur, or CTL-induced mutations in vulnerable regions reduce viral fitness (78,79). In ARV-suppressed patients, the lack of viral replication negates the issue of ongoing viral escape, though sequence diversity in the existing reservoir is an important consideration.…”
Section: Ctl-mediated Approaches For Eradication Of Hiv Infectionmentioning
confidence: 99%
“…DCA has successfully been used to identify intradomain (23)(24)(25)(26)(27) and interdomain (16,17,23,28) contacts in proteins, including the prediction of a transient HK/RR complex that is within crystallographic accuracy of the experimentally determined structure (6). Other recent statistical methods have also been applied to sequence coevolution to explore a diverse range of topics ranging from protein structure and function (29)(30)(31)(32)(33)(34)(35) to the evolutionary fitness of HIV (36). Extending the predictive power of DCA beyond structure prediction, a recent study by Procaccini et al (37) demonstrated that the direct couplings inferred from DCA can be used to quantify interaction specificity among HK and RR proteins.…”
Section: Significancementioning
confidence: 99%